Design of Internet Of Things (IoT) trainer kit with Multi Communication - Era Madona; Efrizon; Anggara Nasution; Rara Yetrisia; Laxsmy Devy (Politeknik Negeri Padang, 2023)
Industry 4.0, or the Fourth Industrial Revolution, is a recent technological development that has significantly changed the industrial production process. One of the keys to this change is the Internet of Things (IoT), where the role of humans is likely to diminish and be replaced by machines. Aligning the workforce with IoT is important, but creating a qualified workforce is a challenge. IoT learning modules are needed to help students understand IoT concepts. The purpose of this research is to design an Internet of Things kit module with Radio communication with LoRa SX1278 Ra-02. The research stages start from literature study, hardware design, software design and overall testing. Module testing is done by sending DHT11 sensor data using LoRa SX1278 Ra-02 and monitored in Thingspeak. From the test results that have been carried out, it can be concluded that sending using LoRa (Long Range) technology is influenced by distance and obstacles. At a distance of 40 to 230 metres, communication between the Lora Transmitter and Lora Receiver is successful, which shows that LoRa technology is able to overcome communication distances in that range. However, at a distance of more than 230 metres to 300 metres, data transmission can still be done by the Lora Transmitter, but the data cannot be received by the Lora Receiver, indicating a bottleneck in communication.